Comparison of the Effect of Intolerance of Ambiguity on the Tendency Toward Cigarette Smoking and Electronic Vaping in Bipolar Adolescents and Adolescents with Risky Behaviors - Sohrabi, Fatemeh; Shahbazi, Negare; Nezami Rashid, Shahnaz; Shadfar, Zahra; Rezagholi, Fariba (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effect of intolerance of ambiguity on the tendency toward cigarette smoking and electronic vaping in bipolar adolescents and adolescents with risky behaviors.Materials and Methods: This study was descriptive–correlational and cross-sectional in design. Path analysis and multi-group analysis (MGA) were conducted using SmartPLS version 4 to examine the relationships within the model. The study population included all adolescent students in Tehran during November to December 2024. A purposive sampling method was employed, and the sample consisted of 68 participants (34 bipolar adolescents and 34 adolescents with risky behaviors). The research instruments included the “Multiple Stimulus Types Ambiguity Tolerance Scale” (MAT) and the “Adolescent Cigarette and E-Cigarette Susceptibility Tendency” (ACSV T) questionnaire. Data were analyzed using SPSS version 27 and the Mann–Whitney U test. The significance level was set at 0.05.Findings: The overall model results indicated that intolerance of ambiguity had a significant negative effect on the tendency toward cigarette smoking (β = −0.640, T = 7.628, p < 0.001) and electronic vaping (β = −0.846, T = 28.607, p < 0.001). The MGA results revealed a significant difference between the two groups in the effect of intolerance of ambiguity on the tendency toward cigarette smoking (p = 0.006), with a stronger effect observed in adolescents with risky behaviors (β = −0.894, p < 0.001) compared to bipolar adolescents (β = −0.535, p = 0.003). However, no significant difference was found between the groups in the path from intolerance of ambiguity to the tendency toward electronic cigarette use (p = 0.353).Conclusion: The findings indicate that intolerance of ambiguity plays a significant role in adolescents’ tendency toward cigarette smoking and electronic vaping, with a stronger effect observed among adolescents with risky behaviors compared to bipolar adolescents. These results highlight the importance of addressing cognitive factors such as ambiguity tolerance in prevention programs, decision-making skills training, and the reduction of risky behaviors. It is recommended that educational and psychological interventions focusing on improving ambiguity tolerance be developed to reduce addictive behaviors among adolescents.